Reproductive technologies as population control: how pronatalist policies harm reproductive health in South Korea. Issue 2 (31st May 2019) - Kim, Sunhye
Abstract: Through the examination of pronatalist policies introduced in South Korea within the last decade, the aim of this commentary is to assess how such policies could harm women's reproductive health if they are practiced only for the purpose of population control. South Korea is a country with one of the lowest fertility rates in the world, and to increase population growth, since 2005, the Korean government has heavily regulated and promoted the use of reproductive technologies, including abortion technologies and assisted reproductive technologies (ARTs). This represents a dramatic shift from South Korea's historically antinatalist position: from the 1960s to the 1980s, abortion was widely practiced and encouraged by the government to reduce population growth, and the use of ARTs went unsupported by the government. However, when the total fertility rate reached 1.08 in 2005, the government strictly prohibited abortion and started promoting the use of ARTs to increase the nation's birthrate. Although under the current pronatalist policies, the Korean government has provided unprecedented incentives to couples seeking to have children, such as expanded maternal/paternal leave and childcare benefits, ironically, reproductive health indicators, such as maternal mortality and infant mortality, have not improved and, in some cases, have even worsened because the pronatalist policies fail to consider women's reproductive health and rights issues.